2019
DOI: 10.1111/famp.12458
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relations between Emerging Adults’ Representations of Relationships with Mothers, Fathers, and Romantic Partners

Abstract: This study employed a fully cross-lagged, longitudinal model to examine reciprocal relations between representations of relationships with parents and romantic partners at ages 20 and 22. Representations were assessed with continuous measures of dismissing/avoidant and preoccupied relationship styles across the attachment and affiliation systems for parents, and across the attachment, affiliation, and caregiving systems for romantic partners. Earlier relationships with both mothers and fathers independently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mothers. Developmental theories emphasize mothers' role in development (Ainsworth, 1989;Erikson, 1993;Suh & Fabricius, 2020), and more recent studies continue to reflect the positive impact of maternal relationships on children's mental health outcomes. For example, perceived maternal support has predicted fewer depressive symptoms among adolescents, as well as buffered the relationship between romantic stress and depressive symptoms (Anderson et al, 2015).…”
Section: Parental Relationshipsmentioning
confidence: 99%
“…Mothers. Developmental theories emphasize mothers' role in development (Ainsworth, 1989;Erikson, 1993;Suh & Fabricius, 2020), and more recent studies continue to reflect the positive impact of maternal relationships on children's mental health outcomes. For example, perceived maternal support has predicted fewer depressive symptoms among adolescents, as well as buffered the relationship between romantic stress and depressive symptoms (Anderson et al, 2015).…”
Section: Parental Relationshipsmentioning
confidence: 99%
“…Parenting has a very important role in the development of a child's personality and interpersonal relationships. Suh et al (2019) confirmed that the quality of the father-son relationship is the basis of knowledge for individuals to form healthy romantic relationships. Individuals build an internal working model or an understanding of self-worth to be loved and believe in others.…”
Section: Literature Reviewmentioning
confidence: 73%
“…However, fewer studies have considered the unique effect of fathers and the changes in the relationship from the perspective of an emerging adult. However, it has been found that for emerging adults, relationship anxiety with fathers and avoidance with romantic partners were reciprocally related (Suh & Fabricius, 2020). This association was not found with mothers, which highlights an interesting aspect of the importance fathers hold in emerging adults' lives and how their relationships with their fathers can influence other significant relationships.…”
Section: Fathermentioning
confidence: 89%